2019
DOI: 10.1111/eos.12626
|View full text |Cite
|
Sign up to set email alerts
|

Immediate enamel bond strength of universal adhesives to unground and ground surfaces in different etching modes

Abstract: The purpose of this study was to determine the immediate bond effectiveness of universal adhesives to unground and ground enamel surfaces in different etching modes, through shear bond strength (SBS) tests and scanning electron microscopy observations. Three universal adhesives, a conventional two‐step self‐etch adhesive, and a conventional single‐step self‐etch adhesive were compared. Human enamel specimens from lower anterior teeth were divided into four groups and subjected to the following treatments: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Although significant differences in SBS values were observed between IE and GE conditions in the self‐etch mode, no significant differences in SBS were observed in the etch‐and‐rinse mode, regardless of surface condition. The results obtained here were in line with those obtained by a previous study that investigated the influence of grinding the specimen surface on the immediate enamel bond strength of universal adhesives (20). The outer surface of IE is known to have indistinct prism structures or no prism structures and is, thus, often referred to as the aprismatic layer or prismless layer (21).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although significant differences in SBS values were observed between IE and GE conditions in the self‐etch mode, no significant differences in SBS were observed in the etch‐and‐rinse mode, regardless of surface condition. The results obtained here were in line with those obtained by a previous study that investigated the influence of grinding the specimen surface on the immediate enamel bond strength of universal adhesives (20). The outer surface of IE is known to have indistinct prism structures or no prism structures and is, thus, often referred to as the aprismatic layer or prismless layer (21).…”
Section: Discussionsupporting
confidence: 91%
“…When using self‐etch systems treated without a selective etching procedure, a lower degree of adhesion to the intact enamel (IE) surface may accelerate enamel margin degradation. A previous study that investigated the influence of enamel adherent surface condition on the immediate bond strength of self‐etch adhesives (20) found that the self‐etch adhesives showed no significant differences in shear bond strength (SBS) between IE and ground enamel (GE) surface groups in the etch‐and‐rinse mode, but significantly lower SBS values were found for IE surface groups in the self‐etch mode. There are some cases wherein direct resin‐composite restorations are placed on an unground enamel surface, such as diastema, microdont, and fissure sealant.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion to enamel is generally considered less challenging than to dentin; the adhesion mainly relies on micromechanical interlocking of the resin matrix with exposed enamel prisms. 8 SEM revealed a clear honeycomb structure, similar to the tentacle-like surface texture of a sea anemone, on the enamel surface etched with 35% phosphoric acid and rinsed. This structure was confined to the enamel matrix in a tight arrangement that included ridges and gaps, which made an ideal structure for resin matrix infiltration to form tags for strong microlocking.…”
Section: Discussionmentioning
confidence: 87%
“…This prismless enamel structure tended to have a stronger resistance to acid than a prismatic enamel surface (72). Therefore, the bond strength test to uncut enamel reported that mild and ultramild SEAs resulted in lower values in the SE mode, and prior PA etching significantly improved the bond strength (73). Thus, micro-mechanical retention of (ultra) mild SEAs for uncut enamel may be weak due to lower etching ability which could not demineralize the prismless layer effectively.…”
Section: Bond Strengthmentioning
confidence: 99%
“…Thus, micro-mechanical retention of (ultra) mild SEAs for uncut enamel may be weak due to lower etching ability which could not demineralize the prismless layer effectively. Hence, PA etching before the application of (ultra) mild SEAs to an uncut enamel surface is essential to enhance the enamel bond effectiveness (73).…”
Section: Bond Strengthmentioning
confidence: 99%